Will the people of Ngawi be able to solve the stunting problem this year? - Rismay Pratama, Della (BKM Public Health and Community Medicine, 2021)
Stunting in the middle to lower class population in Ngawi Regency only relies on agriculture as their main livelihood. Socio-economic conditions experienced by people living in Ngawi Regency affect the high stunting rate in Ngawi Regency. The majority of the people of Ngawi Regency live their livelihoods and only rely on agriculture, so the poverty rate is still high. Ngawi Regency must be able to look for other opportunities that can support improvements in the economic standard for the community. Families with low socioeconomic status will prioritize the need for foods that contain carbohydrates on the grounds of being full, regardless of the quality of food that supports growth (Priyanti and Syalfina, 2018). The ability of families to meet food needs, both in quantity and nutritional quality, dramatically influences the nutritional status of children. Families with relatively fixed incomes, an underweight prevalence, and a lower prevalence of shortness compared to families with irregular incomes (Ministry of Health, 2010). Mistakes in adopting healthy behavior will affect people's beliefs of the hereditary nature of short stature. This belief can cause parents of children and society at large into a passive attitude, namely only accepting the existing conditions; so they are forced to bear all the consequences of stunting until the child grows up. Whereas if there is no improvement within the 1000 days of the first life period, then the long-term impact will be attached to the child when he grows up because the damage during this critical period cannot be corrected after that period has passed. The belief that there is caused by a lack of messages of health promotion on the prevention of stunting risk that makes communities continue adhering to the social perception blame heredity as the cause of stunting (Liem et al.,2019) The nutritional status of children under five can influence the occurrence of stunting and is influenced by the social environment as indications of socio-economic disparities in society, the existence of differences in the location of residence (ecosystem environment) where they live and develop will produce different behavior. Situations like this can have consequences in patterns and widespread malnutrition problems that lead to stunting child-rearing and implications for the development and quality of life of children (Manongga, 2013). The community is also unable to deal with the environmental conditions in which they live because of the economic limitations they experience. Nutritionists must implement a sensitive nutrition intervention framework to address the problem of stunting. This intervention is carried out through various development activities outside the health sector and contributes to 70% of stunting interventions. To overcome the problem of stunting in socio-economic conditions, local governments can do it by looking for other opportunities that can improve the community’s economic level by increasing market-oriented agribusiness activities (quantity, quality, and continuity (Mangowal, 2013). Resolution of health problems in environmental factors then it can be done by providing and ensuring access to clean water through the PAMSIMAS program (Archda and Tumangger, 2019) Stunting pada penduduk kalangan menengah ke bawah di Kabupaten Ngawi yang hanya mengandalkan pertanian sebagai mata pencaharian utama. Kondisi sosial ekonomi yang dialami oleh masyarakat yang tinggal di Kabupaten Ngawi mempengaruhi tingginya angka stunting di Kabupaten Ngawi. Keluarga dengan sosial ekonomi rendah akan lebih mengutamakan kebutuhan pada makanan yang mengandung karbohidrat dengan alasan hanya supaya kenyang, tanpa melihat kualitas makanan yang menunjang pertumbuhan. Kesalahan dalam mengadopsi perilaku sehat akan akan memperngaruhi keyakinan masyarakat bahwa postur pendek merupakan keturunan. Keyakinan tersebut dapat menyebabkan orangtua anak maupun masyarakat secara luas ke dalam sikap pasif, yaitu hanya menerima kondisi yang ada. Kerangka intervensi gizi sensitif harus dilakukan untuk mengatasi permasalahan stunting. Intervensi ini dilakukan melalui berbagai kegiatan pembangunan di luar sektor kesehatan dan berkontribusi pada 70% Intervensi stunting.